Introducing Less-Invasive Surfactant Administration into a Level IV NICU: A Quality Improvement Initiative - Steven M. Conlon; Allison Osborne; Julie Bodie; Jaime Marasch; Rita M. Ryan; Tara Glenn (MDPI AG, 2021)
Less-invasive surfactant administration (LISA), a newer technique of delivering surfactant via a thin catheter, avoids mechanical ventilation. LISA has been widely adopted in Europe but less so in the US. Our goal was to increase the percentage of surfactant delivered via LISA from 0% to 51% by 12/2020. Project planning and literature review started 12/2019, and included a standardized equipment kit and simulation training sessions. We began Plan-Do-Study-Act (PDSA) cycles in 6/2020. Initial exclusions for LISA were gestational age (GA) <28 weeks (w) or ≥36 w, intubation in the delivery room, or PCO2 >70 if known; GA exclusion is now <25 w. From 6 to 12/2020, 97 patients received surfactant, 35 (36%) via LISA. When non-LISA-eligible patients were excluded, 35/42 (83%) received LISA successfully. There were only 2/37 patients for whom LISA was not able to be performed. Three LISA infants required mechanical ventilation in the first week of life. Sedation remained an initial challenge but improved when sucrose was used routinely. LISA was safely and successfully introduced in our NICU.